INCLUSIVE EDUCATION AND ITS IMPLEMENTATION IN MODERN SCHOOLS (KONFERENSIYA, 2025)
Inclusive education has become an essential part of modern schooling, aiming to provide equal learning opportunities for all students, regardless of their abilities, backgrounds, or special needs. This article explores the principles of inclusive education, its importance in contemporary schools, and strategies for effective implementation. It emphasizes the role of teachers, school management, and supportive learning environments in fostering inclusion. Storytelling is highlighted as a teaching method that helps contextualize grammar, instructions, and learning material to make it more engaging for all students. The findings indicate that inclusive practices enhance academic achievement, social development, and emotional well-being for learners in modern schools.